2022
DOI: 10.1111/ajr.12938
|View full text |Cite
|
Sign up to set email alerts
|

Co‐creation of a student‐implemented allied health service in a First Nations remote community of East Arnhem Land, Australia

Abstract: Objectives: To co-create a culturally responsive student-implemented allied health service in a First Nations remote community and to determine the feasibility and acceptability of the service.Design: Co-creation involved a pragmatic iterative process, based on participatory action research approaches. Feasibility and acceptability were determined using a mixed-method pre/postdesign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Interprofessional education in rural settings fosters teamwork and improves care quality (Reed et al 2021), and in First Nations communities, enhances cultural competence and culturally sensitive care (Thackrah et al 2017). Additionally, student-led clinics in rural and remote Australia provide essential health care and engage local communities (Campbell et al 2020;Barker et al 2022); internationally, these clinics have demonstrated high patient satisfaction (Fröberg et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interprofessional education in rural settings fosters teamwork and improves care quality (Reed et al 2021), and in First Nations communities, enhances cultural competence and culturally sensitive care (Thackrah et al 2017). Additionally, student-led clinics in rural and remote Australia provide essential health care and engage local communities (Campbell et al 2020;Barker et al 2022); internationally, these clinics have demonstrated high patient satisfaction (Fröberg et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The key theme from these articles is non‐Indigenous researchers allying with First Nations communities to ensure that cultural values are infused into the research. Of note is the study that produced ‘the first research project to develop a co‐design practice model in the context of a rurally located Aboriginal well‐being Program.’ 9 The authors of this article provide some idea of their positionality, as do many articles where the focus is First Nations peoples 10–16 …”
mentioning
confidence: 99%
“…9 The authors of this article provide some idea of their positionality, as do many articles where the focus is First Nations peoples. [10][11][12][13][14][15][16] We wonder, should positionality be a component of all rural health research articles, and what should be considered in positionality statements?…”
mentioning
confidence: 99%
See 2 more Smart Citations